CFD Simulation of a Temperature Control System for Galvanizing Line of Metal Band Based on Jet Cooling Heat Transfer - Giovanni Carozzo; Carlo Cravero; Martino Marini; Matteo Mazza (Applied Sciences, 2020)
The work focuses on the development of a thermo-fluid dynamic simulation model of a section of close cooling, called a jet cooler, inserted in the galvanizing line of metal band production. Two models of increasing accuracy have been tested and calibrated by experimental data. Special attention to turbulence modeling and boundary conditions has been given. A literature survey was focused on the jet impingement process (the reference heat transfer mechanism for the system component) and on available correlations to predict the heat exchange coefficient. The numerical simulation of jet impingement has been applied to a module of an actual industrial cooler for steel band production. The operation of the jet cooler was simulated in real operating conditions to get a detailed insight into the jet impingement mechanism in order to optimize the heat transfer and reduce, as far as possible, the cooling fluid mass flow rate. The comparison of heat transfer correlations, used in industrial preliminary design, with detailed CFD results is discussed.